Feature Extraction Techniques for Iris Recognition System: A Survey (International Journal of Innovative Research in Computer Science & Technology, 2020)
The extraction of features involves the  method of converting the original pixel values of an image  to more meaningful, useful and measurable information  that can be used in other techniques, such as image  processing, pattern recognition and machine learning. The  feature extraction plays a predominant role in iris  recognition in which also the recognition rate is  determined. The effective recognition accuracy, reduction  of misclassification of two iris templates mostly depends on  feature extraction techniques. An efficient iris recognition  system requires that the discriminating information  presents in an iris pattern to be accurately obtained. This  paper performed a literature review on different techniques  of feature extraction of iris recognition. The  recommendation was made on how these techniques can be  further enhanced to produce an effective iris recognition  system.
Keywords: Biometrics; Computer vision; Feature extraction; Pattern recognition.